Influence of lifestyles on physical, psychological, and cognitive co-morbidity among older adults with diabetes in rural area - Bai, Minfu; Miao, Yudong; Wei, Jingming; Shen, Zhanlei; Zhu, Dongfang; Zhang, Jingbao; Bai, Junwen; Ren, Ruizhe; Guo, Dan; Tarimo, Clifford Silver; Zhang, Jiajia; Cui, Jinxin; et al. (Frontiers in Public Health, 2025)
BackgroundThe association between lifestyles and the co-occurrence of physical, psychological, and cognitive conditions in older adults living with diabetes, especially in rural settings, remains unclear. This study investigated the prevalence of co-morbidity and their association with lifestyle in a rural population of older adults with diabetes.MethodsFrom 1st July to 31 August 2023, a cross-sectional study based on the whole cluster sampling method was conducted in Jia County, Henan Province, China. Participants included adults aged ≥65 years. Lifestyle factors assessed included physical activity, diet, smoking, sleep, and social participation. Physical disease was defined as the presence of one or more chronic conditions, while psychological and cognitive disorders were measured using validated scales. Co-morbidity refers to the occurrence of physical, psychological, cognitive diseases. Depending on the number of diseases, we define different comorbidity status. The subgroups of subdivision included eight categories: no co-morbidity, physical co-morbidity, psychological co-morbidity, cognitive co-morbidity, and their four combinations. Logistic regression models were employed to estimate the association between lifestyles and co-morbidity. The net difference in lifestyle between co-morbidity categories was determined using the propensity score matching (PSM).ResultsAmong 6057 participants, the overall prevalence of physical, psychological, and cognitive co-morbidity was 86.08%. Regular physical activity, adequate sleep, healthy diet, and active social participation were associated with lower prevalence of co-morbidity. A one-unit increase in the lifestyle score was associated with a 34% (OR: 0.66, 95%CI: 0.61–0.72) reduction in the odds of physical-psychological-cognitive co-morbidity. PSM analyses showed significant differences in lifestyle factors and scores across different co-morbidity status.ConclusionGiven the higher prevalence of co-morbidity in rural area and the positive association of lifestyle with co-morbidity status, multifactorial lifestyle interventions should be prioritized within diabetic populations to reduce the risk and burden of co-occurring conditions.